Vision of the Hoped-for Globalization - Urban, Augustyn Marek (Acta Agraria Debreceniensis, 2002)
The author analyzes the issue raised in the title in a phylosophical context from the ontological point of view, which is a branch of phylosophy. As it is known, ontology is „the science of existence”, in other words, a science on the nature of every existing thing.The argumentations indicated by the title do not include „everything”, only those problems which are the most important in the author’s opinion. These are as follows:a) the aim of globalization, to which we refer to here as „hoped-for globalization”,b) the evaluation of the world in which we live,c) the reasons for the birth of the functioning world,d) the activities leading the world to the direction of the hoped-for globalization.The author is aware of his position’s deficiencies, but thinks that the importance of the topic makes it neccessary to create the ideal future’s vision through discussion.